Erythrocyte Osmotic Fragility in Sheep Affected By Eperythrozoon Ovis - Hassan, Marina (2002)
A cross-sectional study design was conducted to detect the eperythrozoonosis in Malaysia environment. Twenty-five sheep were randomly selected from which sixty-two blood samples were collected. Ethylene diamine tetracetic acid (EDTA), flouride and plain vacutainer tubes (Becton Dickinson, USA) were used to collect blood from the jugular vein of sheep. The fresh blood from EDTA was used to prepare thin blood smears, stained with Wright's stain and examined microscopically under x40 and xl00 magnification, to detect the presence of haemoparasites. The E. ovis scoring was determined as 0, positive 1, 2 and 3 to observe the severity of parasitaemia. The fresh blood was also used to determine haematology parameter tests such as white blood cell (WBC), red blood cell (RBC), packed cell volume (PCV), haemoglobin, mean corpuscular volume (MCV), mean corpuscular haemoglobin concentration (MCHC), icterus index and plasma protein determination. Serum and plasma were also taken for clinical biochemistry parameter tests such as the concentrations of glucose, cholesterol, triglyceride, serum gamma glutamyl transferase (yGT) and blood urea nitrogen (BUN). Plasma from the flouride tubes was used for the glucose test. All the data obtained from the sheep were analysed using a correlation test and ANOVA test. The study showed that WBC, RBC, haemoglobin, PCV, MCV, MCHC, icterus index and plasma protein were correlated with the different parasitaemia score. There was no significant difference (p< 0.05) in the haematology parameters of animals with different parasitaemia scores. However, a correlation analysis showed a correlation between the haematology parameters and parasitaemia at different times of infection. The WBC, RBC, haemoglobin, PCV and plasma protein parameters were negatively correlated with the parasitaemia after eight days of infection. The MCV was positively and MCHC was negatively correlated with parasitaemia after four days of infection. There was no significant difference in the concentrations of glucose, cholesterol, yGT and BUN parameters of animals with different parasitaemia scores. But, triglyceride was significantly difference with different parasitaemia scores. However, a correlation analysis showed correlation between the clinical biochemistry parameters and parasitaemia at different times of infection. Glucose levels were negatively correlated with the parasitaemia after four days of infection. Cholesterol levels were negatively correlated with the parasitaemia after two days of infection. yGT and BUN were positively correlated after four days of infection. Triglyceride were negatively correlated after 10 days of infection. The clinical biochemistry parameters showed that the E. ovis activity on the RBC membrane did not affect the parameters studied. There was no significant difference in the erythrocyte osmotic fragility (EOF) with different parasitaemia score. The mean EOF graph showed the same trend in all parasitaemia score. The haematology parameters such as RBC, haemoglobin, PCV, MCV and icterus index were positively correlated whereas the MCHC and plasma protein were negatively correlated with the EOF. Glucose, triglyceride and yGT levels were positively correlated whereas cholesterol and BUN levels were negatively correlated with the EOF. The histopathology changes in the spleen, liver and kidney were mild to moderate. It showed that extravascular haemolysis occurred in the E. ovis infection. In conclusion, the E. ovis detected in Malaysia did not greatly affect the haematology parameters, clinical biochemistry parameters and EOF. However, the effects of E. ovis infection were detected in spleen, liver and kidney. In conclusion, the E. ovis found in Malaysia was mildly pathogenic.